Joint Intra and Multiple Description Coding for Packet Loss Resilient Video Transmission - Kazemi, Mohammad; Iqbal, Razib; Shirmohammadi, Shervin (IEEE transactions on multimedia, 2018)
Multiple description coding (MDC) is a technique for video transmission over error prone networks where the descriptions are routed over multiple paths. Intra coding such as MDC provides error resiliency but coding in this mode must be decided with care since it degrades the compression ratio. In this paper, we present our investigation results for a new intra coding approach in MDC. We have found that, in MDC streams, the best policy is to encode selective frames as I-frame instead of coding some macroblocks of frames in intra mode. In order to find the most suitable I-frame positions within a given video stream, we developed a cost function based on which intra/inter frame type is decided. The MDC scheme with the proposed intra coding criterion, with and without redundancy optimization, is implemented in the H.264/AVC reference software, JM16.0. Based on the experimental performance evaluation, we show that our method achieves higher average PSNR compared to the other optimized MDCs found in the literature.